Denitrification rates in tidal marsh soils: The roles of soil texture, salinity and nitrogen enrichment. (14th April 2020) - Hu, Minjie; Peñuelas, Josep; Sardans, Jordi; Huang, Jiafang; Xu, Kang; Tong, Chuan
Abstract: The denitrification rates of freshwater and oligohaline tidal marsh soils with different textures (loam and sandy soils) in a subtropical estuary, and their responses to nitrogen (N) loading, were investigated. In both marshes, the denitrification rates varied significantly with the season only in loam soil. The denitrification rates were highest in oligohaline marsh loam soil and lowest in freshwater marsh sandy soil. NH4 NO3 addition significantly increased the denitrification rates of all the marsh soils. Our findings suggest that soil texture, soil organic matter (OM) content and low‐level increases in salinity all had large effects on denitrification, indicating that the dynamics of denitrification rates in estuarine marshes with low‐level salinity were controlled by the interaction of salinity and soil texture but mainly depended on OM content. We propose that denitrification in tidal marshes plays an important role in regulating current and future N loading into estuary and inshore coastal waters, especially for tidal freshwater marshes, which introduces great uncertainty into the N dynamics of estuaries under global changes. Highlights: Denitrification rates were higher in loam than sandy soil, independent of salinity. Denitrification rates were higher in oligohaline marsh loam than freshwater marsh loam. Exogenous N input enhanced denitrification in estuarine marsh soil. Loam with high N enhanced N removal, especially in freshwater environments.